Assessing Postoperative Complications in Emergency Bowel Resection and Anastomosis - Anwar, Fawad; Ullah, Jamil Salamat; Maqbool, Adil; Umer, Waleed; Khan, Waseem Ahmed; Bashir, Shaza (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate postoperative Complications in Emergency Bowel Resection and Anastomosis Study Design: Cross-sectional Analytical Study Place and Duration of Study: General Surgical Ward, Combined Military Hospital and Pakistan Emirates Military Hospital, Rawalpindi, Pakistan, from Mar to Aug 2023. Methodology: A total of 110 participants, both genders, who underwent emergency bowel resection and anastomosis for various diseases were selected using a non-probability consecutive sampling technique. The participants were divided into three groups, A, B, and C, according to Clavien-Dindo classification system. Data on clinical characteristics, postoperative results, intraoperative variables, and demographics were gathered and analyzed. Results: Of the 110 patients, 79.1% (n=87) were male and 20.9% (n=23) were female. The mean age was 53.83±9.76 years. Surgical site infections (28.2%), anastomotic leaks (9.1%), post-op ileus (34.5%), and sepsis (21.8%) were among the most frequent postoperative sequelae. Group-B had the most anastomotic leak rate (18.1%), Group-C had the highest surgical site infection rate (43.4%). Group-C was predominantly affected by post-operative ileus (44.8%), and Group-B had the highest sepsis incidence (39.3%). A hospital stay of 7.3±2.7 days was average. Group-B had the greatest death rate of 24.2%, accounting for 12.7% of the total thirty-day mortality. Conclusion: Recognizing the potential complications following an emergency intestinal resection is vital for enhancing surgical outcomes and improving patient care. By employing a multidisciplinary approach, timely detection and effective treatment of these challenges can be ensured, ultimately leading to better recovery and overall patient well-being.